2022
DOI: 10.1037/pha0000428
|View full text |Cite
|
Sign up to set email alerts
|

The effects of artificially induced proestrus on heroin intake: A critical role for estradiol.

Abstract: This study demonstrates that estradiol decreases heroin intake, suggesting that estrogen-based pharmacotherapies may be beneficial to women with opioid use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, more recent studies have reported that estradiol reduces heroin seeking across multiple experimental conditions (Sedki et al, 2015;Vazquez et al, 2020). Results from our laboratory are consistent with these most recent studies, given that we have shown that opioid self-administration is reduced during proestrus in an estrogen but not progesterone dependent manner (Lacy et al, 2016;Smith et al, 2020a;Smith et al, 2020b). Similar processes are likely responsible for the reduction in heroin-maintained responding in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, more recent studies have reported that estradiol reduces heroin seeking across multiple experimental conditions (Sedki et al, 2015;Vazquez et al, 2020). Results from our laboratory are consistent with these most recent studies, given that we have shown that opioid self-administration is reduced during proestrus in an estrogen but not progesterone dependent manner (Lacy et al, 2016;Smith et al, 2020a;Smith et al, 2020b). Similar processes are likely responsible for the reduction in heroin-maintained responding in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately one week after surgery, rats were transferred to heroin self-administration chambers that served as home cages during drug self-administration testing. At this time, estrous phase monitoring began as described previously (Lacy et al, 2016; Smith et al, 2020b). Briefly, approximately one hour prior to the start of each self-administration session, samples of vaginal cells were obtained via vaginal lavage and examined under light microscope to classify as metestrus, diestrus, proestrus, or estrus.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations